Correction to: An Evaluation of Alternative Multiple Testing Methods for Finance Applications (The Review of Asset Pricing Studies, 2022)
This is a correction to: Campbell R Harvey, Yan Liu, Alessio Saretto, An Evaluation of Alternative Multiple Testing Methods for Finance Applications, The Review of Asset Pricing Studies, Volume 10, Issue 2, June 2020, Pages 199–248, https://doi.org/10.1093/rapstu/raaa003In the originally published version of this manuscript, there was a reporting error. In section “2.3.1 Sample size, signal to noise, and power” the text “As shown in both Tables 2 and 3, the biggest impact of increasing power is on the FNDP for which we observe a decrease in both average and standard deviation when moving from low to high power for all procedures. For example, the FNDP of BH decreases from 21% to essentially zero when the sample size increases from 250 to 1,000 monthly observations.” should read “As shown in both Tables 2 and 3, the biggest impact of increasing power is on the FNDP for which we observe a decrease in both average and standard deviation when moving from low to high power for all procedures. For example, the FNDP of BH decreases from 2.3% to essentially zero when the sample size increases from 250 to 1,000 monthly observations.”